A survey of China's renewable energy economy - Ma, H.; Oxley, Leslie; Gibson, J.; Li, W. (Elsevier Science Ltd, 2010)
This paper surveys China's renewable energy economy, focusing particularly on renewable energy laws and programs, the lessons that can be learnt from the current literature, and the implications of that literature. Gaps in the literature on China's renewable energy economy include the need for more comprehensive econometric studies. The literature may also benefit from more collaboration between renewable energy economists and agricultural economists. © 2009 Elsevier Ltd. All rights reserved.